2009
DOI: 10.1063/1.3263948
|View full text |Cite
|
Sign up to set email alerts
|

Fivefold annealing twin in nanocrystalline Cu

Abstract: Fivefold annealing twin has been observed in nanocrystalline Cu at zero external stress. The microstructure of the multifold twins at various annealing temperatures has been examined by transmission electron microscopic in detail. Contrary to the well known sequential twinning mechanism, coherent twin boundaries formed via migration of grain boundary segment were proposed to be the dominant mechanism of fivefold annealing twin, which associated with grain growth during annealing. Moreover, the possibilities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…26) [70]. Fivefold twins were often observed to form by the nucleation and growth mechanism in nanosized particles, annealed nc fcc metals, or nano-wires [229][230][231][232][233]. However, these fivefold growth twins are very different from the fivefold deformation twins discussed here, which are formed by the partial-dislocation mediated sequential twinning mechanism.…”
Section: Sequential Twinning Mechanismmentioning
confidence: 75%
“…26) [70]. Fivefold twins were often observed to form by the nucleation and growth mechanism in nanosized particles, annealed nc fcc metals, or nano-wires [229][230][231][232][233]. However, these fivefold growth twins are very different from the fivefold deformation twins discussed here, which are formed by the partial-dislocation mediated sequential twinning mechanism.…”
Section: Sequential Twinning Mechanismmentioning
confidence: 75%
“…4). In fact, similar structural units were observed after annealing the material for 20 min at 600°C [16]. However, the performed annealing treatments were obviously not sufficient to create 5-fold twins, which are expected to be energetically the most favourable configuration.…”
Section: Fig 3: Pole Figures Of the Structural Unit (Subset Of 5 Gramentioning
confidence: 53%
“…The presence of twins and other low-Σ boundaries (use of coincidence site lattice (CSL) description [13]) in the microstructure is known to significantly improve mechanical properties (grain boundary engineering). Related to a high twin density, 5-fold twins have been observed for different materials [14][15][16]. However, also structural units including other low-Σ boundaries than twins have been reported [17,18].…”
Section: Introductionmentioning
confidence: 97%
“…The formation mechanism of multiple twins is different from that of parallel twins. Several multiple twin mechanisms have been proposed in nc fcc metals, involving sequential twinning mechanism [6], self partial-multiplication twinning mechanisms [7] and grain boundary (GB) segments migration mechanism [8]. According to these mechanisms, the formation of twofold twins, namely V-shaped multiple twins (V-MTs), is an initial and crucial unit to form other multiple twins.…”
Section: Introductionmentioning
confidence: 99%
“…The nanotwins in face-centered-cubic (fcc) metals used for studying outstanding properties and grain size effect are usually related to parallel twins. However, multiple twins with various morphologies have been observed frequently in nanocrystalline (nc) fcc metals, such as twofold and fivefold multiple twins [6][7][8]. Niu et al [9] reported that multiple twins produce a more significant strengthening effect than single twins, because the intersecting twin boundaries (TBs) in the multiple twins can impede the dislocation motion from various directions.…”
Section: Introductionmentioning
confidence: 99%